Physiologic Changes in the Heart Following Cessation of Mechanical Ventilation in a Porcine Model of Donation After Circulatory Death: Implications for Cardiac Transplantation. Issue 3 (11th December 2015) - White, C. W.; Lillico, R.; Sandha, J.; Hasanally, D.; Wang, F.; Ambrose, E.; Müller, A.; Rachid, O.; Li, Y.; Xiang, B.; Le, H.; Messer, S.; et al.
Abstract: Hearts donated following circulatory death (DCD) may represent an additional source of organs for transplantation; however, the impact of donor extubation on the DCD heart has not been well characterized. We sought to describe the physiologic changes that occur following withdrawal of life‐sustaining therapy (WLST) in a porcine model of DCD. Physiologic changes were monitored continuously for 20 min following WLST. Ventricular pressure, volume, and function were recorded using a conductance catheter placed into the right (N = 8) and left (N = 8) ventricles, and using magnetic resonance imaging (MRI, N = 3). Hypoxic pulmonary vasoconstriction occurred following WLST, and was associated with distension of the right ventricle (RV) and reduced cardiac output. A 120‐fold increase in epinephrine was subsequently observed that produced a transient hyperdynamic phase; however, progressive RV distension developed during this time. Circulatory arrest occurred 7.6±0.3 min following WLST, at which time MRI demonstrated an 18±7% increase in RV volume and a 12±9% decrease in left ventricular volume compared to baseline. We conclude that hypoxic pulmonary vasoconstriction and a profound catecholamine surge occur following WLST that result in distension of the RV. These changes have important implications on the resuscitation, preservation, and evaluation of DCD hearts prior to transplantation. Abstract : The authors investigate physiologic changes that occur following withdrawal of life‐sustaining therapy in a porcine model of donation after circulatory death, and demonstrate that hypoxic pulmonary vasoconstriction and a profound catecholamine surge cause right ventricular distension that has important implications on the resuscitation, preservation, and evaluation of these hearts prior to transplantation.